PENGARUH DOSIS FRUKTOSA TERHADAP INDEKS MASSA TUBUH, PROFIL GLUKOSA DARAH DAN KADAR TRIGLISERID (Studi pada Tikus Wistar yang Diinduksi High Fat Fructose Diet ) - Sunarti, Sunarti; Astuti, Fardhiasih Dwi; Bintanah, Sufiati (Jurnal Gizi, 2021)
Fructose or often called fruit sugar is one part of simple carbohydrates calledFructose or often called fruit sugar is one part of simple carbohydrates called monosaccharides (Almatsir 2009). Currently, many food and beverage industries use fructose sugar as a sweetener. (Prahstuti 2011). Consumption of high-fructose products of more than 85 grams per day or more than 25% of caloric needs can lead to increased triglyceride levels and insulin resistance (Prahastuti 2011). The purpose of this study was to evaluate changes in obesity status, fasting blood glucose levels and triglyceride levels in wistar rats induced with a high fat fructose diet, by giving different doses.Research methods.The design in this study was a Randomized Control Trial (RCT), double bline pre post control design using male wistar rats, aged 6-7 weeks weighing 90-150 grams, totaling 15 individuals divided into 3 groups. Group 1 is a group of rats fed HFFD with 1% fructose, group 2 is rats fed HFFD with 2% fructose, group 3 is rats fed standard feed. Before the treatment, adaptation was carried out for 1 week, after that a pre-test was carried out which included measurements of body weight, body length, fasting data glucose levels, and triglyceride levels. The treatment was given for 60 days, in the middle the measurements of body weight, length, fasting data glucose levels, and triglyceride levels were also carried out. The research location was in the clinical pathology laboratory, Faculty of Pharmacy, Muhammadiyah University, Surakarta.The results of the study The administration of fructose at a dose of 2% / kg BW increased fasting blood glucose and triglyceride levels higher than the administration of 1%. kgBB. Upgrade has started since day 30Keywords: Fructose dose, Body Mass Index, fasting blood glucose level, Triglyceride level, Wistar rats, induced High fat fructose diet